2023
DOI: 10.1097/ana.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Remimazolam in Neurosurgery and in Patients With Neurological Diseases: A Narrative Review

Abstract: Remimazolam is a novel ultrashort-acting benzodiazepine that produces sedation by acting as a positive allosteric modulator of the gamma-amino butyric acid-A receptor. Its high water solubility and metabolism via tissue esterases allow for a rapid onset of sedation/anesthesia and prompt arousal despite prolonged use. In addition, the effects of remimazolam can be reversed with flumazenil. This narrative review discusses the role of remimazolam in patients undergoing neurosurgical and neuroradiological procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Thus, remimazolam postconditioning might produce effective postresuscitation cerebral protection through the inhibition of inflammation, oxidative stress, apoptosis, and necroptosis. In addition, recent studies have observed several adverse effects and adverse reactions of remimazolam administration including decreased blood pressure and respiratory frequency, increased blood bilirubin, dizziness, headache, delirium, and delayed neurocognitive recovery (29,30), which should be paid more attention when considering its use in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, remimazolam postconditioning might produce effective postresuscitation cerebral protection through the inhibition of inflammation, oxidative stress, apoptosis, and necroptosis. In addition, recent studies have observed several adverse effects and adverse reactions of remimazolam administration including decreased blood pressure and respiratory frequency, increased blood bilirubin, dizziness, headache, delirium, and delayed neurocognitive recovery (29,30), which should be paid more attention when considering its use in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, remimazolam has been introduced in clinical practice. Remimazolam is a new ultrashort-acting benzodiazepine with high water solubility and metabolism via tissue esterases [137]. Few reports exist on the use of remimazolam during IONM.…”
Section: Anesthesia During Ionmmentioning
confidence: 99%
“…Remimazolam has exhibited a lower incidence of hypotension, reduced vasopressor requirements, and fewer instances of bradycardia compared to propofol-based TIVA (Doi et al 2020). Remimazolam would be quite appealing in patients undergoing cerebrovascular surgery because early emergence from anesthesia is critically important for early neurological assessment and maintaining perfusion pressure is essential to prevent cerebral ischemia in this population (Teixeira et al 2024).…”
Section: Introductionmentioning
confidence: 99%